Safety and immunogenicity of the purified Vero rabies vaccine next generation in chinese Pediatric (≥ 10 years) and adult populations (Revista de Educação Continuada em Medicina Veterinária e Zootecnia do CRMV-SP, 2013)
The Purified Vero cell Rabies Vaccine Next Generation (PVRV-NG) is a highly purified vaccine developed with innovative technology and human and animal origin components-free medium. It was shown to be at least as immunogenic as Verorab™ and presented a similar safety profile in a phase II clinical study conducted in France (pre exposure regimen). A phase III clinical study was performed in Chinese pediatric (≥ 10 years) and adult populations in simulated post-exposure regimen to further document PVRV-NG in comparison to Verorab™.